Handbook of biomass valorization for industrial applications - Ul Islam, Shahid; Shalla, Aabid Hussain; Khan, Salman Ahmad (Hooboken, NJ Wiley, 2022)
The handbook provides a comprehensive view of cutting-edge research on biomass valorization, from advanced fabrication methodologies through useful derived materials, to current and potential application sectors. Industrial sectors, such as food, textiles, petrochemicals and pharmaceuticals, generate massive amounts of waste each year, the disposal of which has become a major issue worldwide. As a result, implementing a circular economy that employs sustainable practices in waste management is critical for any industry. Moreover, fossil fuels, which are the primary sources of fuel in the transportation sector, are also being rapidly depleted at an alarming rate. Therefore, to combat these global issues without increasing our carbon footprint, we must look for renewable resources to produce chemicals and biomaterials. In that context, agricultural waste materials are gaining popularity as cost-effective and abundantly available alternatives to fossil resources for the production of a variety of value-added products, including renewable fuels, fuel components, and fuel additives.
Energy, Biofuels and Bio-Aromatics. Photocatalytic Biomass Valorization into Valuable Chemicals / Brajesh Kumar, Lovjeet Singh, Pawan Rekha, Pradeep Kumar
Biobased Aromatics-Challenges and Opportunities for Development of Lignin as Future Building Blocks / S Samraj, K Senthilkumar, B Bharathiraja
Biofuels and Fine Chemicals From Lignocellulosic Biomass: A Sustainable and Circular Economy / Sushma, Shivangi Chamoli, Sreedevi Upadhyayula, Firdaus Parveen
Carbon-Based Catalysts for Biorefinery Processes: Carbon-Based Catalysts for Valorization of Glycerol Waste From Biodiesel Industry / Pawan Rekha, Lovjeet Singh, Brajesh Kumar, Indu Chauhan, Satyendra Prasad Chaurasia
Catalysts for Conversion of Lignocellulosic Biomass Into Platform Chemicals and Bio-Aromatics / Anjireddy Bhavanam, Poonam Gera, Nitin Naresh Pandhare, Subhrajeet Dash
Pyrolysis of Triglycerides for Fuels and Chemical Production / Luana Marcele Chiarello, Tuanne Gomes Porto, Gabriel Henrique Wienhage, Vanderleia Botton, Vinicyus Rodolfo Wiggers
Drying of Agro-Industrial Residues for Biomass Applications / Hugo Perazzini, Maisa Tonon Bitti Perazzini
Extraction Characterization and Production of Biofuels From Algal Biomass / Neeraj, Yadav Shashikant
Valorization of Biomass Derived Aldehydes Into Oxygenated Compounds / Komal Kumar, Sreedevi Upadhyayula
Food, Agricultural and Environmental Sectors. Advancements in Chemical and Biotechnical Approaches Towards Valorization of Wastes From Food Processing Industries / S Lakshmi Sandhya Rani, R Vinoth Kumar
Photocatalytic Biomass Transformation into Valuable Products / Jasmita Chauhan, SB Rathod, Gaurav Sanghvi, Vidya Patil-Patankar
Organic Materials Valorization: Agro-Waste in Environmental Remediation, Phytochemicals, Biocatalyst and Biofuel Production / S Samraj, K Senthilkumar, D Balaji
Valorization of Secondary Metabolites in Plants / Vidya Patil-Patankar, Pallavi Yadav-Bhagwat, Pradnya Kedari
Functional and Digestibility Properties of Native, Single, and Dual Modified Rice (Oryza sativa L.) Starches for Food Applications /hah Asma Iftikhar, Himjyoti Dutta
Valorization of Agricultural Wastes: A Step Toward Adoption of Smart Green Materials with Additional Benefit of Circular Economy / Kiran Jeet, Vinay Kumar, Anushree, Raman Devi
Valorization of Agricultural Wastes: An Approach to Impart Environmental Friendliness / S Wazed Ali, Satyaranjan Bairagi, Debarati Bhattacharyya
Valorization of Biomass Into Value-Added Products and Its Application Through Hydrothermal Liquefaction / Chitra Devi Venkatachalam, Sathish Raam Ravichandran, Mothil Sengottian
Industrial Applications of Cellulose Extracted from Agricultural and Food Industry Wastes / Sumira Rashid, Himjyoti Dutta
Valorization of Lignin Toward the Production of Novel Functional Materials / Anjireddy Bhavanam, Raghavendra Gujjala, G Srinivasu, Shakuntala Ojha
Characterization and Valorization of Sludge From Textile Wastewater Plant for Positive Environmental Applications / Shumaila Kiran, Abdul Ghaffar, Sarosh Iqbal, Sadia Javed, Nosheen Aslam, Muhammad Asim Rafique, Zohra Zreen, Gulnaz Afzal, Nusrat Parveen, Saba Naz
Impact of Biofertilizers in Sustainable Growth of Agriculture Sector / Prajwalita Pathak, Kankan Kishore Pathak, Arun Kumar Pathak
Valorization of Agricultural Wastes as Low-Cost Adsorbents Towards Efficient Removal of Aqueous Cr(VI) / Rashmi Acharya, Kulamani Parida
Index
Includes index.
Keywords: Biomass chemicals; Biomass conversion